Fuzzy Logic-Based Medical Decision System for Diagnosing Chronic Obstructive Pulmonary Disease - Gurpreet Singh Popli; Praveen Arora (Research Highlights in Disease and Health Research Vol. 7, 2023)
This paper proposes a fuzzy logic-based medical decision system for diagnosing COPD, which utilizes fuzzy sets to represent the severity of symptoms, medical history, and test results, and fuzzy rules and reasoning to generate a diagnostic result as output. The proposed system aims to provide a more accurate and nuanced understanding of a patient’s condition, which could help doctors track changes in the patient’s condition and adjust treatment accordingly. The proposed study involves collecting data from a sample of COPD-diagnosed patients and developing and testing the fuzzy logic-based medical decision system. It is essential to note that fuzzy logic-based medical decision systems should be used in conjunction with other medical expertise and tools to ensure the best possible patient outcomes. A fuzzy logic-based medical decision system for COPD diagnosis has the potential to improve the accuracy and efficiency of COPD diagnosis, leading to better patient outcomes and quality of life.